An Archaeological Evaluation at Spring Cottage Farm, Alconbury, Cambridgeshire - Whittaker, Paula (Cambridge Archaeological Unit, Department of Archaeology, University of Cambridge, 1997)
An archaeological evaluation was undertaken by Cambridge Archaeological Unit at land beside Spring Cottage Farm, Alconbury , Cambridgeshire. This work was commissioned by Wroxall Properties Ltd. in advance of a proposed housing development on the site of 0.8 hectares. The preliminary results revealed evidence of at least two phases of activity. The earliest phase broadly dates to the Late Saxon/Medieval periods (9th-14th centuries), represented by a droveway, field boundary ditches and probable structural remains. Later activity is evidenced in the form of previously unrecorded ridge and furrow earthworks. These were undatable by artefacts but are historically known to have been cultivation techniques of Medieval and Post-Medieval agricultural activity.